Comparison of Surgical Intervention and Mortality for Seven Surgical Emergencies in England and the United States. Issue 5 (November 2019) - Markar, Sheraz R.; Vidal-Diez, Alberto; Patel, Kirtan; Maynard, Will; Tukanova, Karina; Murray, Alice; Holt, Peter J.; Karthikesalingam, Alan; Hanna, George B.
Abstract : Objective: To examine differences between England and the USA in the rate of surgical intervention and in-hospital mortality for 7 index surgical emergencies. Background: Considerable international variation exists in the configuration, provision, and outcomes of emergency healthcare. Methods: Patients aged <80 years hospitalized with 1 of 7 surgical emergencies (ruptured abdominal aortic aneurysm, aortic dissection, appendicitis, perforated esophagus, peptic ulcer, small bowel or large bowel, and incarcerated or strangulated hernias) were identified from English Hospital Episode Statistics and the USA Nationwide Inpatient Sample (2006–2012) and classified by whether they received a corrective surgical intervention. The rates of surgical intervention and population mortality were compared between England and the USA after adjustment for patient demographic factors. Results: From 2006 to 2012, there were 136, 047 admissions in English hospitals and 1, 863, 626 admissions in US hospitals due to the index surgical emergencies. Proportion of patients receiving no surgical intervention, for all 7 conditions was greater in the England (OR 4.25, 1.55, 8.53, 1.92, 2.06, 2.42, 1.75) and population in-hospital mortality was greater in England (OR 1.34, 1.67, 2.22, 1.65, 2.7, 4.46, 3.22) for ruptured abdominal aortic aneurysm, aortic dissection, appendicitis, perforated esophagus, peptic ulcer, small bowel or large bowel, and incarcerated or strangulated hernias respectively. In England (where follow-up was available), lack of utilization of surgery was also associated with increased in-hospital and long-term mortality for all conditions. Conclusion: England and US hospitals differ in the threshold for surgical intervention, which may be associated with increases in mortality in England for these 7 general surgical emergencies. Abstract : Supplemental Digital Content is available in the text